EMPOWERMENT OF THE JANGGALA VILLAGE TP PKK THROUGH TRAINING IN SEWING, ENTREPRENEURSHIP, FINANCIAL MANAGEMENT, AND BATIK PRODUCT DIVERSIFICATION - Hartono, Rudi; Fadilah, Mohamad Fazar; Awaludin, Adila; Asnani, Ari; Dwiasi, Dian Windy; Adawiyah, Wiwiek Rabiatul (LPPM Univ. Ibn Khaldun Bogor, 2026)
Janggala Village in Tasikmalaya Regency is designated as a national priority area characterized by relatively high poverty rates and susceptibility to natural disasters. As a strategic community group, the Family Welfare Empowerment Team (TP PKK) of Janggala Village encounters significant challenges, specifically low entrepreneurial skills, limited access to production equipment, and weak business management governance. This empowerment program aims to enhance the partners' economic independence by strengthening production capabilities (hard skills) and business management competencies (soft skills). The implementation method utilized a participatory